2021
DOI: 10.3390/ma14247776
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatibility and Degradation Behavior of Molybdenum in an In Vivo Rat Model

Abstract: The biocompatibility and degradation behavior of pure molybdenum (Mo) as a bioresorbable metallic material (BMM) for implant applications were investigated. In vitro degradation of a commercially available Mo wire (ø250 µm) was examined after immersion in modified Kokubo’s SBF for 28 days at 37 °C and pH 7.4. For assessment of in vivo degradation, the Mo wire was implanted into the abdominal aorta of female Wistar rats for 3, 6 and 12 months. Microstructure and corrosion behavior were analyzed by means of SEM/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 34 publications
1
17
0
Order By: Relevance
“…After 22 weeks, the micro-CT images confirm that almost all of the Mo resorbs in the body, and the concentration of Mo in the spleen also begins to decrease. In the brain, the concentration of Mo saturates after 22 weeks of implantation, and we expect them to be decreased at a later time point, as previously reported (38).…”
Section: Bioresorbable and Biocompatible Mo Electrodes In Vivosupporting
confidence: 79%
“…After 22 weeks, the micro-CT images confirm that almost all of the Mo resorbs in the body, and the concentration of Mo in the spleen also begins to decrease. In the brain, the concentration of Mo saturates after 22 weeks of implantation, and we expect them to be decreased at a later time point, as previously reported (38).…”
Section: Bioresorbable and Biocompatible Mo Electrodes In Vivosupporting
confidence: 79%
“…However, the close fit of the fractured parts and the fact that no new degradation product layer has formed beneath the monolithic layer shows that the cracks do not form in situ, but after removal of the samples from the immersion medium and drying. The cracking of the degradation product layer during drying has been illustrated in the Supplementary Information of Schauer et al [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the next steps, the in vivo biocompatibility and the exact degradation rates in complex organisms must be investigated. While Sikora-Jasinska et al showed the biocompatibility and degradation behavior in a flowing system [ 5 ] and Schauer et al demonstrated degradation in the abdominal aorta of rats [ 33 ], the behavior as an osteosynthesis system should be investigated separately. In particular, the degradation and dissolution behavior of molybdenum sheet metal should be investigated under in vivo conditions consistent with implant applications in craniomaxillofacial surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4] By contrast, magnesium (Mg), Zinc (Zn), Tungsten (W), Iron (Fe), Molybdenum (Mo) have been identified as the main alternative choices, due to their biocompatibility and easy of disposal. [6] The sourcing of biodegradable semiconductor materials is another pressing issue in order to reduce e-waste. [5] So far, Ultra-Thin Silicon (UTS) has been used to manufacture biodegradable devices, but silicon electronic manufacture is known to be energy intensive from Life Cycle Assessments (LCAs) studies.…”
Section: Introductionmentioning
confidence: 99%